Struktur dan Fungsi Ritual Malabuh pada Masyarakat Banjar Kalimantan Selatan Kajian Folklor - Mahmudah Mahmudah; Nina Queena Hadi Putri (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Ritual Malabuh In Banjar Community of South Kalimantan. This study aimed to determine the structure, function, and to analyze the ritual of malabuh meaning in Banjar community, South Kalimantan. In examining this problem, researchers used a qualitative research with descriptive method. Sources of data in this study were some data of ritual that obtained from 10 informants who have experience in performing malabuh ritual. Data collection techniques used interview through recording the spoken by informants. Data analysis used transcription, identification, classification, and inference of data to determine the structure, function, and meaning of ritual. The result of the research concludes that the structure of the malabuh ritual has a structure consisting of one (1) verse, which is a maximum of 7 lines and a minimum of 1 line. This ritual have the complete sentence structure and have structural elements consisting of greeting, intention, and purpose. Ritual of malabuh was functioned as an introduction or a tool to invoke God's power, either directly or through an intermediary by the mystical crocodile which is believed have the power to provide protection or to eliminate the disturbance. The ritual that analyzed with hermeneutic approach performed significantly as a communication medium for serving malabuh ritual offerings.